2015
DOI: 10.1007/s13197-015-1958-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and temperature influence on honey texture properties

Abstract: The aim of this study is to evaluate the chemical composition and temperatures (20, 30, 40, 50 and 60°C) influence on the honey texture parameters (hardness, viscosity, adhesion, cohesiveness, springiness, gumminess and chewiness). The honeys analyzed respect the European regulation in terms of moisture content and inverted sugar concentration. The texture parameters are influenced negatively by the moisture content, and positively by the°Brix concentration. The texture parameters modelling have been made usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
0
10
2
Order By: Relevance
“…40.5 and 80%, respectively) occur along with an almost equal glucose/fructose ratio (Devillers et al, 2004). Oroian et al (2016) found that the textural parameters were negatively influenced by the sum of the fructose and glucose and the ratio of these two compounds. According to White (1974), honey granulation is enhanced at temperatures from 13 to 15.5°C, but this process is retarded at temperatures below 0°C.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…40.5 and 80%, respectively) occur along with an almost equal glucose/fructose ratio (Devillers et al, 2004). Oroian et al (2016) found that the textural parameters were negatively influenced by the sum of the fructose and glucose and the ratio of these two compounds. According to White (1974), honey granulation is enhanced at temperatures from 13 to 15.5°C, but this process is retarded at temperatures below 0°C.…”
Section: Resultsmentioning
confidence: 82%
“…Stelmakienė et al (2012) assessed the rheological characteristics of Lithuanian honey and found very close and significant correlations between thixotropy and the index of flow consistency (direct), and between thixotropy and the flow behaviour index (inverse), however, no detailed data were provided by authors. Oroian et al (2016) reported that all studied typical TPA textural properties (hardness, adhesion, cohesiveness, springiness, gumminess, chewiness) and the viscosity of Romanian honeys were substantially positively influenced by one another (p < 0.001), and that the correlation coefficients were between 0.815 and 0.999. Similar and very close relationships for viscosity and other TPA parameters were also reported by Oroian et al (2017) in subsequent investigations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar effect of temperature on honey texture properties was reported by Oroian et al . (). In their report, the hardness of honey measured by texture profile analysis (TPA) technique, which is comparative to the firmness value in this study, reduced with increasing temperature.…”
Section: Resultsmentioning
confidence: 97%
“…The multilayer perceptron (MLP) is the most commonly used ANN for solving prediction tasks. MLP compared to polynomial model was employed by Oroian et al [15] for modeling relationships between honey chemical composition and textural properties. ANN model accuracy determined by R 2 values ranged between 0.92 and 0.99, and was slightly worse than accuracy of polynomial model.…”
Section: Introductionmentioning
confidence: 99%